Zooplankton Taxonomic and Trophic Community Structure Across Biogeochemical Regions in the Eastern South Pacific - González, Carolina E.; Escribano, Rubén; Bode, Antonio; Schneider, Wolfgang (Frontiers in Marine Science, 2019)
Biochemical conditions and taxonomic composition of size-fractioned mesozooplankton were studied after a cruise conducted in September 2015 between the Chilean coast (70°W) and Easter Island (110°W) within the central south Pacific gyre. Taxonomy was assessed with an automated method based on image analysis and biochemical conditions assessed by analyses of C and N contents and stable isotope composition. Based on surface Chlorophyll-a levels, four regions were distinguished across the zonal gradient: eutrophic (Chilean upwelling zone), mesotrophic (Coastal Transition Zone), oligotrophic (open ocean water) and ultraoligotrophic (central south Pacific gyre). The zones had marked differences in temperature, oxygen, salinity and Chlorophyll-a, and they also exhibited significant differences in zooplankton composition, C/N ratios and13C and 15Nfor all size fractions of zooplankton. Variability in the sources of C and N, linked to biogeochemical processes, such as new production and denitrification in the upwelling zone, potential diazotrophy, highly regenerated C and N and extreme oligotrophy (N-deficiency) in oceanic areas, are suggested as the key drivers of these differences. Our findings also suggest a strong coupling between taxonomic and size zooplankton-diversity and the sources of nutrients that fuel phytoplankton, the major food source for zooplankton. Although multiple factors and processes can modulate C and N and their isotopes composition of zooplankton biomass, our study shows that changes in community structure are linked to different biogeochemical regions across the zonal gradient, providing the basis for ecological zonation associated with nutrient utilization at lower trophic levels.